2013 Curriculum: Assessment of Minimum Competencies in Freedom Learning and education 4.0 Context - Hidayatulloh, Muhammad Kris Yuan; Susila, I Wayan; Rijanto, Tri (International Journal for Educational and Vocational Studies, 2020)
This study aims to offer alternative competency assessments based on Freedom Learning policies and education era 4.0 through the implementation of the 2013 revised curriculum. The minimum competency assessment refers to skills needed in the 21st century through student-oriented learning models, character values in the 2013 curriculum, and HOTS items with reference to literature studies. To improve students' literacy and numeracy skills in the minimum competency assessment, an appropriate approach to the competency assessment is needed, namely by implementing student-centered learning models. Some of these models have been widely discussed in a study. The results show that the role of students is greater in the learning, while the teacher acts as a supervisor. The implementation of the learning through the project learning approach also contains observation and analysis from students. So that competency assessment based on literacy and numeracy can be carried out comprehensively. Implementation of the National Examination which tends to use learning material from student textbooks will only cause students, teachers and student guardians to be burdened with time, energy, and mind. The competency assessment instrument as a substitute for the national assesment requires progressive learning, not necessarily memorization but observation and analysis. Thus, students are required to deal directly with the object of learning material.